Isolation and Antioxidant Activity of Caffeic Acid from Roots of Bryophyllum pinnatum (Lam.) Kurz. - Sharma, Abhishek; Chandra, Naresh (Asian Journal of Chemistry, 2016)
Bryophyllum pinnatum (Lam.) Kurz. (Crassulaceae) is a perennial shrub, which possess bioactive phytoconstituents viz. terpenoids, phenolic compounds, flavonoid, anthraquinone, saponin and known to cure diabetes, cancer and act as anti-inflammatory, antiulcer, antihyperlipidemia. In the present study, isolation and antioxidant activity of caffeic acid from roots of Bryophyllum pinnatum (Lam.) Kurz. was carried out. Caffeic acid was characterized by TLC, FTIR and was elucidated by 1H NMR and 13C NMR technique. DPPH radical scavenging power of isolated caffeic acid showed IC50 value 66.58 ± 0.49 μg/mL in comparison to aqueous extract of root (139.52 ± 2.62 μg/mL).